Phase change energy storage material with controllable heat release and long-distance transportation capability and preparation method of phase change energy storage material

By using a combination of polyols, deionized water, tackifiers and photothermal materials in phase change energy storage materials, the problem of poor stability in long-distance transportation by existing phase change energy storage materials is solved, and the stable heat storage performance of the materials in long-distance transportation is achieved, reducing the risk of energy loss and waste.

CN119570454APending Publication Date: 2025-03-07SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411802251.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing phase change energy storage materials have poor stability during long-distance heat transportation, and there is a risk of energy loss and waste.

Method used

A phase change energy storage material with controllable heat release is prepared by a combination of polyols, deionized water, tackifier and photothermal material through a specific mass ratio and preparation method. The material improves the photothermal absorption rate under light conditions, and makes the molecular structure more stable by adding tackifiers, ensuring excellent heat storage performance during long-distance transportation.

Benefits of technology

The stability and heat storage performance of phase change energy storage materials in long-distance transportation have been improved, which reduces the loss and risks in energy transportation, and improves the safety and economicality of energy transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570454A_ABST
    Figure CN119570454A_ABST
Patent Text Reader

Abstract

The invention relates to the field of phase-change energy storage materials, and particularly discloses a heat-release-controllable phase-change energy storage material capable of being transported for a long distance and a preparation method of the heat-release-controllable phase-change energy storage material. The preparation method of the phase change energy storage material comprises the following steps: magnetically stirring polyhydric alcohol and deionized water at 80 DEG C at a rotating speed of 400r / min for 1h, mixing, heating and dissolving; and cooling the obtained solution to room temperature, sequentially adding the tackifier and the photo-thermal material, mixing and stirring for 1 hour, ultrasonically dispersing for 30 minutes, putting into a glass bottle, putting into an air dry oven, drying for 1 hour at the temperature of 120 DEG C, removing excessive water, taking out, and sealing. By adding the photo-thermal material, the photo-thermal absorption rate of polyhydric alcohols contained in the phase change energy storage material can be enhanced under the illumination condition, then the overall performance of the phase change energy storage material is improved, by adding the tackifier, the molecular structure of the phase change energy storage material is more stable, and excellent heat storage performance can be kept during long-distance heat transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of long-distance transport heat storage materials, and in particular to a phase-change energy storage material with controllable heat release and long-distance transportability and a preparation method thereof. Background Art

[0002] Phase change energy storage materials are a type of material that can absorb or release heat from the environment during its phase change process, thereby achieving the purpose of energy storage and release and regulating the mismatch between energy demand and supply. When the ambient temperature changes, the material can maintain the temperature of the system basically constant by absorbing or releasing heat. Since the phase change process can absorb or release heat, the use of phase change thermal storage materials can effectively improve the temperature distribution inside the building and reduce indoor temperature fluctuations, thereby achieving the purpose of energy saving.

[0003] However, faced with the objective condition of mismatch between energy supply and demand, most of the existing publicly available phase change energy storage materials have the problem of poor stability, resulting in the risk of energy loss during long-distance heat transportation; especially in industrial production, a large amount of waste heat is usually wasted due to the difficulty in recovery and long-distance transportation.

[0004] To this end, a phase change energy storage material that can be stably transported over long distances is proposed to reduce losses and risks in the energy transportation process, improve the safety and economy of energy transportation, and achieve effective allocation of energy in time and space, thereby alleviating the instability of energy supply. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a phase-change energy storage material with controllable heat release and long-distance transportability and a preparation method, which solves the problem of poor stability of existing phase-change energy storage materials.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a phase-change energy storage material with controllable heat release and long-distance transport, comprising the following raw materials: polyol, deionized water, a thickener and a photothermal material, wherein the mass ratio of the polyol to the photothermal material is (5-6):1.

[0007] Preferably, the polyol has a melting point range of 100-120° C., a freezing point range of 60-65° C., and a melting enthalpy of 310 J / g.

[0008] Preferably, the photothermal material is at least one of graphene, carbon nanotubes or carbon black, the polyol is any one of neopentyl glycol, pentaerythritol, polyethylene glycol, mannitol and erythritol, and the viscosity enhancer is any one of hydroxypropyl methylcellulose, hydroxyethyl cellulose, xanthan gum and guar gum.

[0009] Preferably, the amount of the tackifier added is 0.5% to 1.5% of the mass of the polyol.

[0010] Preferably, the density of the phase change energy storage material is 1g / cm 3 ~2g / cm 3 , thermal conductivity is greater than or equal to 0.5W / m·K.

[0011] Preferably, the process includes: mixing and stirring the polyol, deionized water, thickener and photothermal material for 1 hour, ultrasonically dispersing for 30 minutes, putting them into a glass bottle, and drying them in a forced air drying oven at 120° C. for 1 hour to remove excess moisture, then taking them out and sealing them to obtain a phase change energy storage material.

[0012] Preferably, before the polyol, deionized water, viscosity enhancer and photothermal material are uniformly mixed, the method further comprises: mixing, heating and dissolving the polyol and the deionized water at 80° C. and 400 r / min with magnetic stirring for 1 h.

[0013] The present invention provides a phase-change energy storage material capable of controllable heat release and long-distance transport and a preparation method thereof.

[0014] It has the following beneficial effects:

[0015] 1. The present invention can increase the photothermal absorption rate of the polyol contained in the phase change energy storage material under illumination conditions by adding photothermal materials, thereby improving the overall performance of the phase change energy storage material, and by adding a thickener, the molecular structure of the phase change energy storage material is made more stable, and excellent heat storage performance can be maintained during long-distance heat transportation. At the same time, the phase change energy storage material of the present invention can release heat under external mechanical triggering conditions, solving the technical problem of poor stability of existing phase change energy storage materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the long-distance transportation stability of the phase change energy storage material of the present invention;

[0017] Figure 2 A schematic diagram of temperature change during long-distance transportation of the phase change energy storage material of the present invention;

[0018] Figure 3 Schematic diagram showing the effect of the molecular weight of the hydroxyethyl cellulose on the viscosity of the phase change energy storage material of the present invention;

[0019] Figure 4 It is a time-temperature curve diagram of the heat absorption and release process of different phase change energy storage materials of the present invention;

[0020] Figure 5 This is a schematic diagram of the thermophysical performance test of the phase change energy storage material DSC of the present invention, Figure 5a is the endothermic peak curve, Figure 5 b is the exothermic peak curve;

[0021] Figure 6 It is a schematic diagram of the long-term thermal storage stability performance of the phase change energy storage material of the present invention;

[0022] Figure 7 is a schematic diagram of the supercooling stability of the phase change energy storage material of the present invention, Figure 7 a is standing at room temperature, Figure 7 b is standing at ultra-low temperature;

[0023] Figure 8 It is a mechanically triggered heat release curve diagram of the phase change energy storage material of the present invention at ambient temperature. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] The embodiment of the present invention provides a phase-change energy storage material with controllable heat release and long-distance transport, comprising the following raw materials: erythritol, deionized water, hydroxypropyl methylcellulose and carbon nanotubes, wherein the mass ratio of erythritol to the carbon nanotubes is 5:1, the amount of hydroxypropyl methylcellulose added is 1% of the mass of erythritol, and the density of the phase-change energy storage material is 1.5 g / cm 3 The thermal conductivity of the phase change energy storage material is 0.8 W / m·K.

[0027] The preparation method of this embodiment comprises the following steps:

[0028] S1. Mix erythritol and deionized water at 80°C and heat to dissolve them at a speed of 400 r / min for 1 h with magnetic stirring;

[0029] S2, cooling the solution obtained in step S1 to room temperature, then adding hydroxypropyl methylcellulose and carbon nanotubes in sequence, mixing and stirring for 1 hour, and ultrasonically dispersing for 30 minutes before placing in a glass bottle;

[0030] S3. Place the mixture in a forced air drying oven and dry it at 120° C. for 1 h to remove excess moisture, then take it out and seal it to obtain a phase change energy storage material.

[0031] Embodiment 2:

[0032] The embodiment of the present invention provides a phase-change energy storage material with controllable heat release and long-distance transport, comprising the following raw materials: erythritol, deionized water, hydroxypropyl methylcellulose and carbon nanotubes, wherein the mass ratio of erythritol to the carbon nanotubes is 5.5:1, the amount of hydroxypropyl methylcellulose added is 1.2% of the mass of erythritol, and the density of the phase-change energy storage material is 1.6 g / cm 3 The thermal conductivity of the phase change energy storage material is 0.7 W / m·K.

[0033] The preparation method of this embodiment comprises the following steps:

[0034] S1. Mix erythritol and deionized water at 80°C and heat to dissolve them at a speed of 400 r / min for 1 h with magnetic stirring;

[0035] S2, cooling the solution obtained in step S1 to room temperature, then adding hydroxypropyl methylcellulose and carbon nanotubes in sequence, mixing and stirring for 1 hour, and ultrasonically dispersing for 30 minutes before placing in a glass bottle;

[0036] S3. Place the mixture in a forced air drying oven and dry it at 120° C. for 1 h to remove excess moisture, then take it out and seal it to obtain a phase change energy storage material.

[0037] Embodiment three:

[0038] The embodiment of the present invention provides a phase-change energy storage material with controllable heat release and long-distance transport, comprising the following raw materials: erythritol, deionized water, hydroxypropyl methylcellulose and carbon nanotubes, wherein the mass ratio of the erythritol to the carbon nanotubes is 6:1, the amount of the hydroxypropyl methylcellulose added is 1.5% of the mass of the erythritol, and the density of the phase-change energy storage material is 1.8 g / cm 3 , the thermal conductivity of the phase change energy storage material is 0.6 W / m·K.

[0039] The preparation method of this embodiment comprises the following steps:

[0040] S1. Mix erythritol and deionized water at 80°C and heat to dissolve them at a speed of 400 r / min for 1 h with magnetic stirring;

[0041] S2, after cooling the solution obtained in step S1 to room temperature, hydroxypropyl methylcellulose and carbon nanotubes were added in sequence, mixed and stirred for 1 hour, ultrasonically dispersed for 30 minutes, and then placed in a glass bottle,

[0042] S3. Place the mixture in a forced air drying oven and dry it at 120° C. for 1 h to remove excess moisture, then take it out and seal it to obtain a phase change energy storage material.

[0043] The phase change energy storage materials prepared in Examples 1 to 3 were tested and evaluated as follows:

[0044] First, 50 g of each phase change energy storage material prepared in Examples 1 to 3 were taken, and the phase change properties of the samples were tested using differential scanning calorimetry (DSC). The results are shown in Table 1.

[0045] Embodiment 1 Embodiment 2 Embodiment 3 Melting point(℃) 108 112 118 Freezing point(℃) 67.6 67.2 66.9 Melting enthalpy (J / g) 310.4 310.1 309.8

[0046] As can be seen from Table 1, the phase change energy storage material provided in the present application has a wide phase change range and a high melting enthalpy, and can be used in a variety of occasions.

[0047] The phase change energy storage material prepared in Example 3 was tested for long-distance transportation stability. The results are as follows: Figure 1 and Figure 2 As shown, after long-distance transportation, the temperature of the phase change energy storage material is still within a stable temperature range.

[0048] Based on the phase change energy storage material prepared in Example 1, hydroxypropyl methylcellulose with different molecular weights (1500, 2500, 3000, 5000, 6400) was used as a raw material to verify the effect of the molecular weight of hydroxypropyl methylcellulose on the viscosity of the phase change energy storage material. The results are as follows: Figure 3 As shown, as the molecular weight of hydroxypropyl methylcellulose increases, the viscosity of the phase change energy storage material increases synchronously.

[0049] Based on the phase change energy storage material prepared in Example 1 (denoted as MHPCMs), the exothermic stability was compared with that of pure erythritol (denoted as ERY) and erythritol + hydroxypropyl methylcellulose composite material (denoted as HPCMs). The results are as follows: Figure 4 As shown, pure erythritol has an exothermic peak during the time-temperature change process, the supercooling is unstable, and the latent heat of phase change is unexpectedly released. It is verified that hydroxypropyl methylcellulose can stabilize the supercooling of erythritol, so that the latent heat of phase change can be stably stored; and the addition of photothermal materials does not affect the stability of supercooling. While increasing light absorption, it can still stabilize the supercooling of the erythritol + hydroxypropyl methylcellulose composite material without releasing additional latent heat of phase change.

[0050] Based on the phase change energy storage materials prepared by adding 0.1g, 0.3g, and 0.5g of hydroxypropyl methylcellulose (denoted as Pcm-2, Pcm-3, and Pcm-4) in Example 1, and comparing with pure erythritol (namely Pcm-1), DSC thermophysical properties tests were performed. The results are as follows Figure 5 As shown, Figure 5 a is the endothermic peak, Figure 5 b is the exothermic peak. The results show that with the increase of the amount of hydroxypropyl methylcellulose added, the endothermic peak and exothermic peak of the phase change energy storage material also increase. The time-temperature change curve of the heat release of Pcm-4 after mechanical triggering is shown in Figure 2. Figure 8 shown.

[0051] Based on the phase change energy storage material prepared in Example 1, it was placed in a static state for a long time and compared with pure erythritol to verify the material stability after long-term placement. The results are as follows Figure 6 shown.

[0052] Pcm-1, Pcm-2, Pcm-3, and Pcm-4 were sealed and placed at room temperature and -20°C for 15 days to verify the supercooling stability of the phase change energy storage material. Figure 7 As shown, Figure 7 a is standing at room temperature, Figure 7 b is static in a -20°C environment. The results show that the phase change energy storage material can not only be stably supercooled at room temperature and store the phase change latent heat for a long time, but also maintain its performance even at an ultra-low temperature of -20°C. The supercooling stability and latent heat storage stability of the composite material are verified from the temperature environment, and the material performance is not affected by different geographical environments.

[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A phase-change energy storage material with controllable heat release and long-distance transportability, characterized in that: The invention comprises the following raw materials: polyol, deionized water, a tackifier and a photothermal material, wherein the mass ratio of the polyol to the photothermal material is (5-6):

1.

2. The phase-change energy storage material with controllable heat release and long-distance transportability according to claim 1, characterized in that: The polyol has a melting point range of 100-120° C., a freezing point range of 60-65° C., and a melting enthalpy of 310 J / g.

3. The phase-change energy storage material with controllable heat release and long-distance transportability according to claim 1, characterized in that: The photothermal material is at least one of graphene, carbon nanotubes or carbon black, the polyol is any one of neopentyl glycol, pentaerythritol, polyethylene glycol, mannitol and erythritol, and the viscosity enhancer is any one of hydroxypropyl methylcellulose, hydroxyethyl cellulose, xanthan gum and guar gum.

4. The phase-change energy storage material with controllable heat release and long-distance transportability according to claim 1, characterized in that: The added amount of the tackifier is 0.5% to 1.5% of the mass of the polyol.

5. The phase-change energy storage material with controllable heat release and long-distance transportability according to claim 1, characterized in that: The density of the phase change energy storage material is 1g / cm 3 ~2g / cm 3 , thermal conductivity is greater than or equal to 0.5W / m·K.

6. A method for preparing a phase-change energy storage material with controllable heat release and long-distance transportability, characterized in that: The method comprises the following steps: mixing and stirring the polyol, deionized water, a thickener and a photothermal material for 1 hour, ultrasonically dispersing the mixture for 30 minutes, placing the mixture into a glass bottle, and drying the mixture in a forced air drying oven at 120° C. for 1 hour to remove excess water, and then taking the mixture out and sealing the mixture to obtain a phase change energy storage material.

7. The method for preparing a phase-change energy storage material capable of controlled heat release and long-distance transport according to claim 6, characterized in that: Before the polyol, deionized water, thickener and photothermal material are uniformly mixed, the method further includes: mixing, heating and dissolving the polyol and the deionized water at 80° C. and at a speed of 400 r / min for 1 hour with magnetic stirring.

Citation Information

Patent Citations

  • Solid-solid phase change material and preparation method thereof

    CN110669475A

  • Polyethylene glycol / hydroxypropyl cellulose carbon nanotube composite solid-solid phase change material and preparation method thereof

    CN110804301A

  • Organic phase change heat storage material and preparation method thereof

    CN112940686A

  • Low-temperature near-eutectic phase change cold storage material and preparation method thereof

    CN115093835A

  • Melting point modified composite phase change heat storage material as well as preparation method and application thereof

    CN118027904A